Psychosocial Experiences Of Mothers Of Preterm Babies Admitted To The Neonatal Intensive Care Unit Of The Upper East Regional Hospital, Bolgatanga: A Descriptive Phenomenological Study. - Daliri, D.B.; Laari, T.T.; Afaya, A.; Amoah, M.A.; et al. (BMJ Open, 2024)
Introduction: The postnatal period often presents significant psychological and social distress for mothers, a burden that is potentially heightened by having a preterm baby. Mothers of preterm babies face various psychosocial challenges that need to be explored. While some studies have explored the experiences of mothers of preterm babies, there is a need for more context-specific research to inform targeted interventions, especially in resource-constrained settings like northern Ghana. This study aimed to explore the psychosocial experiences of mothers of preterm babies admitted to the neonatal intensive care unit (NICU) of the Upper East Regional Hospital, Ghana. Methods: This descriptive phenomenological study was conducted in the NICU of the Upper East Regional Hospital in Ghana. Thirteen mothers of preterm babies were purposively sampled and interviewed using a semi-structured interview guide. The interviews were transcribed verbatim and analysed using Colaizzi’s descriptive phenomenological method. Results: Three themes emerged namely, mothers’ emotional experience, challenges encountered at the NICU and coping strategies. The mothers expressed a range of emotions, from indifference to profound sadness, disbelief, fear and worry, on realising their babies were preterm. Challenges within the NICU were financial constraints and poor NICU facilities while coping strategies included reliance on God, self-reliance and support from family and nurses. Conclusion: Mothers of preterm babies in the NICU experience significant emotional distress and face numerous challenges. Comprehensive support programmes that address financial, emotional and practical needs are essential to improve outcomes for both mothers and their preterm babies.
Research Article
Keywords: Preterm Babies; Neonatal Intensive Care Unit; Upper East Regional Hospital; Mothers